Teegarden’s Star revisited: a nearby planetary system with at least three planets - Dreizler, Stefan; Luque, R.; Ribas, I.; Koseleva, V.; Ruh, H. L.; Nagel, E.; Pozuelos, F. J.; Zechmeister, M.; Reiners, A.; Caballero, J. A.; Amado, P. J.; Béjar, V. J. S.; et al. (Astronomy and astrophysics, 2024)
The two known planets in the planetary system of Teegarden’s Star are among the most Earth-like exoplanets currently known. Revisiting this nearby planetary system with two planets in the habitable zone aims at a more complete census of planets around very low-mass stars. A significant number of new radial velocity measurements from CARMENES, ESPRESSO, MAROON-X, and HPF, as well as photometry from TESS motivated a deeper search for additional planets. We confirm and refine the orbital parameters of the two know planets Teegarden’s Star b and c. We also report the detection of a third planet d with an orbital period of 26.13 ± 0.04 days and a minimum mass of 0.82 ± 0.17 M⊕. A signal at 96 days is attributed to the stellar rotation period. The interpretation of a signal at 172 days remains open. The TESS data exclude transiting short-period planets down to about half an Earth radius. We compare the planetary system architecture of very low-mass stars. In the currently known configuration, the planetary system of Teegarden’s star is dynamically quite different from that of TRAPPIST-1, which is more compact, but dynamically similar to others such as GJ 1002.